Identification and Characterization of Known Biallelic Mutations in the IFT27 (BBS19) Gene in a Novel Family With Bardet-Biedl Syndrome - Schaefer, Elise; Delvallée, Clarisse; Mary, Laura; Stoetzel, Corinne; Geoffroy, Véronique; Marks-Delesalle, Caroline; Holder-Espinasse, Muriel; Ghoumid, Jamal; Dollfus, Hélène; Muller, Jean (Frontiers in Genetics, 2019)
Bardet-Biedl syndrome (BBS; MIM 209900) is a rare ciliopathy characterized by retinitis pigmentosa, postaxial polydactyly, obesity, hypogonadism, cognitive impairment and kidney dysfunction. Mutations in 22 BBS genes have been identified to cause the disease. We report a family with typical BBS features (retinitis pigmentosa, postaxial polydactyly, obesity, cognitive impairment, and atrioventricular septal defect) mutated in IFT27/BBS19. IFT27 is part of the Intraflagellar transport (IFT), a bidirectional mechanism allowing the protein motility within the cilia. Using whole exome sequencing, two compound heterozygous mutations were found in the proband (NM_006860.4:c.[104A > G];[349+1G > T], p.[Tyr35Cys];[?]) consistent with the expected autosomal recessive inheritance mode. These two mutations have already been reported but independently in other families and lacking either familial segregation or functional validation. This is the third report of IFT27 mutations in BBS patients confirming IFT27 as a BBS gene (BBS19). Mutations in IFT genes (IFT27, IFT172 and IFT74) confirm the IFT-pathway as a pathomechanism for BBS.